2020
DOI: 10.1101/gad.335794.119
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regulation of histone modifications and long-range chromosomal interactions during postmitotic transcriptional reactivation

Abstract: During mitosis, transcription of genomic DNA is dramatically reduced, before it is reactivated during nuclear reformation in anaphase/telophase. Many aspects of the underlying principles that mediate transcriptional memory and reactivation in the daughter cells remain unclear. Here, we used ChIP-seq on synchronized cells at different stages after mitosis to generate genome-wide maps of histone modifications. Combined with EU-RNA-seq and Hi-C analyses, we found that during prometaphase, promoters, enhancers, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
113
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(129 citation statements)
references
References 74 publications
(114 reference statements)
8
113
1
Order By: Relevance
“…Here we focus on those that measured nascent transcriptional activity rather than steady-state RNA levels, by assays such as PRO-seq (precision nuclear run on sequencing) ( Core et al., 2008 ; Kwak et al., 2013 ) and EU-RNA-seq (ethyl uridine-labeled RNA sequencing) ( Palozola et al., 2017 ). These studies consistently showed that transcription of genes and enhancers is dramatically downregulated during mitosis but rapidly recovered during G1 entry ( Hsiung et al., 2016 ; Kang et al., 2020 ; Palozola et al., 2017 ; Pelham-Webb et al, 2020 ; Teves et al, 2018 ). Studies in somatic cells also saw a global, transient spike in transcription during mitotic exit, although groups of genes showed distinct kinetics ( Hsiung et al., 2016 ; Palozola et al., 2017 ).…”
Section: Main Textmentioning
confidence: 79%
See 3 more Smart Citations
“…Here we focus on those that measured nascent transcriptional activity rather than steady-state RNA levels, by assays such as PRO-seq (precision nuclear run on sequencing) ( Core et al., 2008 ; Kwak et al., 2013 ) and EU-RNA-seq (ethyl uridine-labeled RNA sequencing) ( Palozola et al., 2017 ). These studies consistently showed that transcription of genes and enhancers is dramatically downregulated during mitosis but rapidly recovered during G1 entry ( Hsiung et al., 2016 ; Kang et al., 2020 ; Palozola et al., 2017 ; Pelham-Webb et al, 2020 ; Teves et al, 2018 ). Studies in somatic cells also saw a global, transient spike in transcription during mitotic exit, although groups of genes showed distinct kinetics ( Hsiung et al., 2016 ; Palozola et al., 2017 ).…”
Section: Main Textmentioning
confidence: 79%
“…Several recent studies have begun characterizing the dynamic resetting of chromatin architecture upon mitotic exit in different cell types ( Abramo et al., 2019 ; Kang et al., 2020 ; Naumova et al., 2013 ; Zhang et al., 2019 ), including mouse naive PSCs ( Nagano et al., 2017 ; Pelham-Webb et al, 2020 ). Nagano et al.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, ChIP-seq in mitotically arrested mESCs demonstrated that H3K27ac was retained at housekeeping gene promoters and stem-cell associated enhancers during mitosis, suggesting that the mark primes transcriptional activation in G 0 /G 1 . Recent data demonstrated H3K4me3 remained associated with most promoters, while H3K27ac was maintained at only a subset of enhancers and promoters, but quickly reestablished at the anaphase/telophase transition (Kang et al, 2020). This was determined using a combinatorial approach with ChIP-seq and EU-RNA-seq, a technique where cells are treated with ethynyl uridine to label newly synthesized RNA, which can then be isolated and sequenced to generate a transcriptome of newly synthesized transcripts.…”
Section: Mitotic Bookmarking: a Brief Primermentioning
confidence: 99%